2019
DOI: 10.7196/sajcc.2019.v35i1.373
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal tube cuff pressure monitoring: Assessing current practice in critically ill patients at Chris Hani Baragwanath Academic Hospital

Abstract: Cuffed tracheal tubes are used to prevent loss of tidal volume during positive pressure ventilation, minimise pulmonary aspiration of gastric and oral secretions, facilitate respiratory monitoring and, in the paediatric population, reduce the need for repeated laryngoscopy due to incorrect tube size. [1][2][3] These goals are achieved by appropriate cuff inflation. Cuff pressure (CP) should be >25 cmH 2 O to prevent aspiration and <30 cmH 2 O to avoid damage to surrounding structures. [4,5] Obstruction to bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…However, the characteristics of the nurses and the study setting were similar to those in most ICUs in Malaysia 38 . Second, this study only reported on knowledge acquisition but did not observe the changes in actual practice as an outcome of learning, so further studies to access the impact of education intervention on practice and compliance are suggested as knowledge acquisition may not guarantee safe practice 16,39 …”
Section: Limitationsmentioning
confidence: 87%
See 2 more Smart Citations
“…However, the characteristics of the nurses and the study setting were similar to those in most ICUs in Malaysia 38 . Second, this study only reported on knowledge acquisition but did not observe the changes in actual practice as an outcome of learning, so further studies to access the impact of education intervention on practice and compliance are suggested as knowledge acquisition may not guarantee safe practice 16,39 …”
Section: Limitationsmentioning
confidence: 87%
“…These recommendations are also part of the preventive measures emphasized in the VAP prevention guidelines 10,11 . Despite the existence of such guidelines, evidence shows that variation in cuff maintenance practices and compliance with such guidelines are still suboptimal in some of the ICUs in developed countries like the United States, 6 Australia, and New Zealand 12,13 and in developing countries like Pakistan, 14 Sri Lanka, 5,15 and South Africa 16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inflated cuff of the endotracheal tube is designed to prevent microaspiration; thus, the cuff pressure should be at a moderate level at 20 to 30 cm of water, as air leakage or aspiration occurs when it is too low, and tracheal or subglottic stenosis occurs when it is too high. [ 5 , 76 , 77 ] In NCC patients, the cuff pressure may decline with extubation and the transition to a prone position. [ 78 ] In addition, the high incidence of pneumonia further emphasized the necessity of determining and monitoring cuff pressure.…”
Section: Respiratory Support In Nccmentioning
confidence: 99%
“…Plato suggested that 'human behaviour flows from three main sources: desire, emotion, and knowledge.' If, as is suggested by Khan et al, [8] we have the knowledge, then our behaviour towards cuff pressure measurement must be for the lack of desire and emotion in this regard. The desire to do or react to something is a function of its immediacy, its seriousness and the degree to which we connect with it.Our challenge is to effect a behaviour change in this regard.…”
mentioning
confidence: 93%